1996
DOI: 10.1104/pp.110.3.845
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Antifreeze Proteins in Winter Rye Leaves, Crowns, and Roots by Tissue Printing

Abstract: During cold acclimation, antifreeze proteins (AFPs) that are similar to pathogenesis-related proteins accumulate in the apoplast of winter rye (Secale cereale L. cv Musketeer) leaves. AFPs have the ability to modify the growth of ice. To elucidate the role of AFPs in the freezing process, they were assayed and immunolocalized in winter rye leaves, crowns, and roots. Each of the total soluble protein extracts from cold-acclimated rye leaves, crowns, and roots exhibited antifreeze activity, whereas no antifreeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 54 publications
2
32
1
1
Order By: Relevance
“…Percentages of total osmolytes present in apoplastic fluid extracted from NH and 1PH tissues were not significantly different from each other (Table I). Even though we found no significant difference in osmolytes in the apoplasts of NH and 1PH oat crowns, others (Marentes et al, 1993;Antikainen et al, 1996) have shown that quantitative changes in proteins do occur in the apoplast of rye leaves during 1PH.…”
Section: Indicators Of Cellular Leakagecontrasting
confidence: 47%
“…Percentages of total osmolytes present in apoplastic fluid extracted from NH and 1PH tissues were not significantly different from each other (Table I). Even though we found no significant difference in osmolytes in the apoplasts of NH and 1PH oat crowns, others (Marentes et al, 1993;Antikainen et al, 1996) have shown that quantitative changes in proteins do occur in the apoplast of rye leaves during 1PH.…”
Section: Indicators Of Cellular Leakagecontrasting
confidence: 47%
“…Cold stress induced an accumulation of soluble proteins in Brassica juncea (Hayat et al 2000(Hayat et al , 2001. Synthesis of specific proteins is an important mechanism involved in increasing freezing tolerance during cold acclimation (Antikainen et al 1996). Low temperature stress increased glucose, starch and sucrose contents (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Several PRs are expressed in cultured cells [6,72] 55], also suggestive of a developmental role. PR-2-like, PR-3-like and PR-5-like proteins accumulate in the apoplast of winter rye tissues during cold acclimation and exhibit antifreeze activity [3]. Basic PR-5 proteins (osmotin) are induced in e.g.…”
Section: Current Status Of the Families Of Pathogenesis-related Proteinsmentioning
confidence: 99%